EDUCATIONAL GAMES USED IN 1ST-2ND GRADE NATIVE LANGUAGE LESSONS, THEIR CONTENT, EFFECTIVENESS AND METHODOLOG ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
In this article, educational games used in 1st-2nd grade mother tongue lessons, their content, effectiveness and methodology are analyzed based on specific sources.